v.2 - Seervai, H. M. (Delhi, 1996)
The reason why H.M. Seervai, the former Advocate-General of Maharashtra, is singled out is not just because his address (in Plenary Sessions) on The Place of Law Officers and Ministers of Justice was, both in content and delivery, a masterpiece, but because he persuaded his hearers to recognise a reality which had been. forced on his refined and scholarly mind by the brutal experience of events in India during the twenty-month period of Mrs. Ghandhi's Emergency. To him, and to countless legal practitioners in Asia. and Africa, the Rule of Law is no cant phrase to be invoked as a talisman against some measure which, for political reasons good or bad, the speaker happens to dislike. Rather it is one of the essential conditions of civilised life. Hence there was a rare authority in the words of H.M. Seervai when he told his audience in the McEwan Hall that prior to the Emergency, India had a Bill of Rights which, along with other legal safeguards of the citizen, was swept away as if it had never been... What (the unhappy Indian experience) does do is to make a lawyer carrying on practice with quiet regularity in Scotland realise that the continued existence of the professional freedom which he takes for granted depends not upon paper charters but upon a widespread conviction that the Rule of Law is a reality and that it must remain a reality. If for no other reason that is why the 5th Commonwealth Law Conference was justified. It is therefore a pity that so few representatives of the host country were present to join the Attorney General for England and Wales in applauding HM Seerval's magisterial repudiation of the heresya heresy which in parts of Africa is alive and well-that a Government lawyer must be committed to the philosophy of the Government which employs him.
Keywords: Constitutional law